Intensified Convection Heat Transfer of Single-Row Bunch of Finned Tubes in an Air Stream: Experimental Study and Generalization of the Obtained Data - A. B. Sukhotskii; G. S. Marshаlоvа (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents method and results of experimental study of the intensified heat transfer for the single-row bunch consisting of bimetallic pipes with spiral knurled ribs with the following parameters: outer diameter of a rib d = 56 mm; rib height h = 15 mm, rib pitch s = 2.5 mm, average thickness of a rib D = 0.5 mm; diameter of a rib at the bottom d0 = 26 mm, coefficient of fins j = 21. The pipes cross pitch S1 in a single-row bunch makes 58, 61, 64 and 70 mm. The intensification of a heat transfer has been arranged in a stream of heated air over an experimental bunch by means of two types of exhaust shaft i.e. the one with adjustable height and the one with the adjustable section through passage. The aim of the work was to perform an experimental study and to summarize the data of a heat transfer of the single-row bunches consisting of bimetallic finned tubes under the intensified (mixed) air convection and also to develop an engineering method of calculation of single-row recirculation air heaters. The results of experimental study of the intensified convective heat transfer of the single-row bunch consisting of bimetallic finned tubes in a stream of heated air are presented in the form of dependences of number of Nusselt on Grashof number and Reynolds number. As a result of generalization of experimental data, the generalized criteria equation for calculation of heat transfer of the single-row bunch consisting of bimetallic finned tubes when cross pitches of installation of tubes, the areas of exhaust outlets and heights of the exhaust shaft are various, has been obtained. The engineering technique for design calculation of the single-row recirculation air heater has also been developed.